Risk factors and outcomes associated with anastomotic leaks following esophagectomy: a systematic review and meta-analysis. Issue 3 (20th January 2020) - Kamarajah, Sivesh K; Lin, Aaron; Tharmaraja, Thahesh; Bharwada, Yashvi; Bundred, James R; Nepogodiev, Dmitri; Evans, Richard P T; Singh, Pritam; Griffiths, Ewen A
Summary: Anastomotic leaks (AL) are a major complication after esophagectomy. This meta-analysis aimed to determine identify risks factors for AL (preoperative, intra-operative, and post-operative factors) and assess the consequences to outcome on patients who developed an AL. This systematic review was performed according to PRISMA guidelines, and eligible studies were identified through a search of PubMed, Scopus, and Cochrane CENTRAL databases up to 31 December 2018. A meta-analysis was conducted with the use of random-effects modeling and prospectively registered with the PROSPERO database (Registration CRD42018130732). This review identified 174 studies reporting outcomes of 74, 226 patients undergoing esophagectomy. The overall pooled AL rates were 11%, ranging from 0 to 49% in individual studies. Majority of studies were from Asia ( n  = 79). In pooled analyses, 23 factors were associated with AL (17 preoperative and six intraoperative). AL were associated with adverse outcomes including pulmonary (OR: 4.54, CI95% : 2.99–6.89, P  < 0.001) and cardiac complications (OR: 2.44, CI95% : 1.77–3.37, P  < 0.001), prolonged hospital stay (mean difference: 15 days, CI95% : 10–21 days, P  < 0.001), and in-hospital mortality (OR: 5.91, CI95% : 1.41–24.79, P  = 0.015). AL are a major complication following esophagectomy accounting for major morbidity and mortality. This meta-analysis identified modifiable risk factors for AL, which can be a target for interventions to reduce AL rates. Furthermore, identification of both modifiable and non-modifiable risk factors will facilitate risk stratification and prediction of AL enabling better perioperative planning, patient counseling, and informed consent.